Monitoring the efficiency of organisation’s internal control and economic security system - O. A. Ageeva; Yu. D. Matytsyna (Вестник университета, 2022)
The article reviews the content and economic role of monitoring financial and economic activities. The aim of the study is to determine the essence of one of the main elements that make up the internal control system, namely: monitoring, which ensures the economic entity economic security. The subject is an indicative monitoring system, with the help of which risks are identified in a certain segment of the enterprise activity, that is, at the micro level. The research methodology consisted in the information collection and generalisation in order to build a scientific hypothesis about the subject under study, as well as in the recommendations development to improve the internal control system efficiency in the direction of ensuring the economic entity economic security. As a result, the authors proposed a monitoring algorithm that ensures the internal control system and economic security effectiveness.